2022
DOI: 10.3389/fmats.2022.1049304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air-entraining agent and polypropylene fiber on the mechanical properties, autogenous shrinkage, and fracture properties of fully recycled aggregate concrete

Abstract: The effects of air-entraining agent (AEA) and polypropylene fiber (PPF) on the autogenous shrinkage and fracture properties of fully recycled aggregate concrete (FRAC) are studied to obtain FRAC with low density, low autogenous shrinkage, and superior fracture properties. Six groups of FRAC with different AEA (0, 5%, 10%) and PPF (0, 1.2 kg/m3) contents were prepared for test. The results illustrate that AEA can slightly reduce density but that it has an adverse effect on the strength and fracture properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Besides surface tension, some studies argue that autogenous shrinkage is affected predominantly by the pore volume below 50 nm [37,38], where a higher pore volume would induce higher drying stress and therefore more shrinkage. Such a relationship was not observed for the copolymer samples of the current study.…”
Section: Autogenous Shrinkagementioning
confidence: 99%
“…Besides surface tension, some studies argue that autogenous shrinkage is affected predominantly by the pore volume below 50 nm [37,38], where a higher pore volume would induce higher drying stress and therefore more shrinkage. Such a relationship was not observed for the copolymer samples of the current study.…”
Section: Autogenous Shrinkagementioning
confidence: 99%
“…Currently, there is limited research on the effect of fiber on fully recycled concrete. Ding et al [ 28 ] reported that the incorporation of PF negatively affected the compressive strength and splitting tensile strength of fully recycled concrete but enhanced the flexural strength and fracture properties. Li et al [ 29 ] observed that basalt fiber improved the bonding performance in recycled aggregate, made the interface strength higher, and enhanced the shear failure of fully recycled concrete when the load grade reached 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Also, BF enhance the tensile and flexural capacities of the cementitious composites that can reduce and delay the cracking caused by shrinkage, thermal variations, and chemical attacks. Polypropylene (PP) fibres have also previously been found beneficial in reducing the shrinkage, thermal cracks, and improving durability 24 , 25 . Therefore, the hybridization of PP fibres with BF can offer desirable characteristics to cementitious composites while ensuring sustainability.…”
Section: Introductionmentioning
confidence: 99%